Urgensi Kompetensi Pedagogik Guru dalam Pembelajaran Abad Ke- 21: Studi Kritis Pedagogik Futuristik - Ariyanti Ariyanti; Yusuf Tri Herlambang; Tatang Muhtar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The quality of our future lives depends on how we prepare for it today. Education plays a crucial role in preparing individuals to be globally competitive. Teachers, as the spearhead of civilization, must bring fresh perspectives in facilitating students to acquire 21st-century skills and competencies. Preparing for this necessitates discussing the urgency of teachers' pedagogical competencies in 21st-century learning through a critical study of futuristic pedagogy. This research will delve into the importance of teachers possessing futuristic pedagogical competencies to prepare for a prosperous life in the 21st century. A critical and comprehensive discussion on pedagogical competencies for 21st-century teachers and futuristic pedagogy theories will be conducted using the library research method to gather relevant data supporting the topic under review. The result of this research is that teachers with pedagogical competencies, particularly futuristic pedagogy, can guide students in developing critical, creative, and collaborative skills that meet 21st-century demands, preparing them to be future leaders and innovators. Therefore, investing in the development of teachers' pedagogical competencies in the context of 21st-century learning and conducting a critical review of futuristic pedagogy is a crucial step in ensuring that education remains relevant and positively impacts the development of students and society as a whole.